PENGARUH SUPERVISI DAN KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU SMA N 1 DUKUPUNTANG KABUPATEN CIREBON - Nono Sudarsono (Oasis : Jurnal Ilmiah Kajian Islam, 2017)
Based on the observation result to the some teachers at SMA N 1 Dukupuntang. The results show that there are many obstacles or issues related to the implementation of Principal supervision and leadership, such as; the poor quality of principal supervision and the type of principal leadership which is not strict to the teacher and staff.Â  The study is based on the understanding that the School as an Institution which is a principal as a top manager should try to grow a good performance of all teachers in order to stimulate and support them to improve their performances. So it will give additional inspiration to develop the teacher performance. The techniques of collecting data are used observation technique, questionnaires and documentation. The data analysis are used a quantitative method and correlationner method. The conclusion of the Research is the quality of principal supervision, the principal leadership, and the teachers performance at SMA N 1 Dukupuntang are low. These are based on the findings of questionnaires recapitulation that majority teacher answered the questionnaires with sometimes. Based on the analysis of the data, the principal supervision and principal leadership give an effect to the teacher performance. It can be seen from the regression test which is the F tabel score is 2,79 < F account 45,089 which means significant. It means that Ha is accepted and Ho is rejected.The significant effect of principal supervision and leadership is 63,9%. This score is based on the determination test ( at Model summary table).Keywords : supervision, the principal leadership, and the teachers performance.